Polymerization Degree of Phytochelatin in Contaminated Soil Phytoremediation of Manganese in Hibiscus Sabdariffa Linn Var Sabdariffa - Mavoungou Ange Younes; Lepengue Alexis Nicaise; M’Batchi Bertrand (European Scientific Journal, ESJ, 2016)
The aim of this study is to determine the usefulness of roselle (Hibiscus sabdariffa L. var sabdariffa), and its polymerization degree of phytochelatins (PCs) for contaminated soil Mn phytoremediation. Sorrel plants grow in three highly contaminated soils Mn (4μM, 6μM and 8μM) in control conditions. Roselle accumulates large amounts of Mn in the leaves in the various contaminated environments Mn. The removal rate of absorption in the higher Mn was observed in the medium 8μM Mn. In parallel, the middle 4μM Mn showed the lowest Mn extraction rate. Induced oxidative stress due to the Mn content, generates the highest level in ascorbate 8μM Mn. The medium 8μM Mn shows an induction of 9 to 16 times the amount of γ-glutamylcysteine and against a low induction of γ- glutamylcysteine in the medium 4μM Mn. Accordingly, the total content phytochelatin (PC) was 7-9 times higher 8μM Mn. In addition, PCs high polymerization degree were observed in 8μM Mn (PC4, PC6 and PC7), while PC2 and PC3 occurred in 4μM Mn and 6μM Mn only. The correlation analysis shows that 8μM Mn phytoremediation capacity is associated with the PCs synthesis and their polymerization degree is high.